Volcanic ash in the water column: Physiological impact on the suspension-feeding bivalve Mytilus chilensis. (February 2018) - Salas-Yanquin, L.P.; Navarro, J.M.; Pechenik, J.A.; Montory, J.A.; Chaparro, O.R.
Abstract: Ashes settling into the sea from volcanic explosions expose suspension-feeding species to reduced seston quality. Adults and juveniles of the mussel Mytilus chilensis were exposed for 15 days to the phytoplankton Isochrysis galbana together with various concentrations of ashes. We then quantified impact on survival and physiology. Although no individuals died during the experiment, by the end of the study clearance rates and oxygen consumption rates had decreased substantially, and tissue weight of mussels exposed to the highest ash concentrations declined substantially. Gills showed no physical damage, but did show abundant mucus secretion in response to ash particles. Moreover, as the relative proportions of microalgae to ash in the diet decreased, individuals showed increasing preferential ingestion of microalgal particles. Increased ash content in the diet altered physiological rates and activated distinct particle selection with a high production of pseudofeces and high energy costs, with potential long-term consequences. Highlights: Volcanic ash particles in diets did not cause mortality during 15 days of exposure. Clearance and oxygen consumption were reduced in mussels exposed to higher volcanic ash concentrations. Mussel gills did not show evident damage from exposure to high ash concentrations, but produced substantial mucus secretions. Exposure to ash particles caused a substantial decline in tissue weight. Electivity index for rejection of ash particles was greater as the proportion of ash to microalgae in the diet was increased.